Energy Efficient Smart Phones for 5G Networks - Radwan, Ayman; Rodriguez, Jonathan (Signals and Communication Technology,, 2015)
This book addresses current technology trends and requirements leading towards the next era in mobile communication handsets; and beyond that the book proposes innovative solutions that could be candidate solutions for 5G phones. It adopts a multidisciplinary and interdisciplinary stance towards handset design, a necessary ingredient if 5th Generation handset and services are to really take-off. Therefore the scope of the book targets a broad range of subjects, including energy efficiency, RF design, cooperation, context-aware systems, roaming, and short-range networking, all of which working in synergy to provide seamless mobility and high speed connectivity within a HetNet environment. Specifically, the authors investigate how we can exploit the cooperation paradigm and context-aware mechanism working in synergy to provide energy compliant phones that can introduce power savings of up to 50% on state-of-the-art. Going beyond this, a chapter on business modeling approaches is also included, based on incentive mechanisms for cooperation that will provide the necessary leverage to promote the up-take of the proposed technology.